The Impact of Using PhET Simulation Through a Multiple-Representation Approach on Students' Learning Outcomes and Interests - Hasbullah, Hasbullah; Muzana, Syarifah Rahmiza; Zulkarnaini, Zulkarnaini; Musriandi, Riki; Dasrita, Dasrita (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study aims to determine the learning outcomes and interests of students with the use of PhET Simulation media through a multiple- representation approach to motion concept. The research method used is a quasi-experiment with a one group pretest and posttest design. The research subjects were taken using a random sampling technique involving 45 grade XI students at SMA Negeri 6 Banda Aceh. The research data was obtained from learning outcomes and student interest questionnaires. Data analysis using a gain test. Based on the results of the study, student learning outcomes were obtained with an average value of multiple representation in verbal, mathematical, graphic formats, and experienced a significant increase. While the overall student interest in learning is in the good category. This study can make students happy, interested, and have attention and direct involvement in the learning process so that it can be suggested to teachers or related parties to consider the use of PhET Simulation through a multi-representation approach in the physics teaching and learning process.